Sistem Informasi Akuntansi Pengeluaran Kas Pada Badan Amil Zakat Nasional (BASNAS) Provinsi Jawa Timur - Rahma Fatimah Santoso; Sutini Sutini; Diana Zuhro; Tjandra Wasesa; Wiratna Wiratna; Heri Toni (Universitas 45 Surabaya, 2023)
The government has established and formed a special institution that handles zakat, infaq and shadaqah funds. The presence of Law No. 23 of 2011 has regulated the centralization of Zakat management and is completely carried out by the state. With the presence of this Law, it is hoped that the potential for zakat can be realized in large amounts, and the management system can be known with certainty. The National Zakat Amil Agency (BAZNAS), which is the main institution that carries out zakat management, is expected to be able and capable of collecting zakat funds as optimally as possible and able to provide open and transparent accountability to muzakki and the community in general. With good management and transparency, muzakki will have a higher level of trust in BAZNAS as a place to distribute Zakat. Management of public finances in the form of zakat, infaq and shadaqah (ZIS) must be carried out carefully, precisely and cautiously. A good financial management system by public institutions including the National Amil Zakat Agency (BAZNAS) reflects the ability and performance of these institutions in managing funds sourced from the community. If the performance produces good results, the community will increasingly receive trust and trust in managing public funds, in this case Zakat, Infaq and Sadaqah (ZIS) funds from Islamic financial sources.